2015
DOI: 10.1093/ecco-jcc/jjv114
|View full text |Cite
|
Sign up to set email alerts
|

The Syk Inhibitor Fostamatinib Decreases the Severity of Colonic Mucosal Damage in a Rodent Model of Colitis

Abstract: Fostamatinib reduced the inflammatory damage in the experimental colitis. This effect may be due to suppression of TNFα, T-lymphocytes, and neutrophils in colonic mucosa via suppression of Syk. Fostamatinib may be an appropriate treatment alternative for ulcerative colitis. Further clinical studies are required to support this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…Syk has been proposed to play a critical role in psoriasis, atherosclerosis, and IBD. The data [39] showed that Syk expression increases in experimental colitis, and fostamatinib, a Syk inhibitor, affects inflammatory cells and proinflammatory cytokines and provides histological and morphological healing of colon mucosa. MI-1 could inhibit Syk in vitro, so its anti-inflammatory effects could be realized through signaling pathways which involve Syk.…”
Section: Discussionmentioning
confidence: 99%
“…Syk has been proposed to play a critical role in psoriasis, atherosclerosis, and IBD. The data [39] showed that Syk expression increases in experimental colitis, and fostamatinib, a Syk inhibitor, affects inflammatory cells and proinflammatory cytokines and provides histological and morphological healing of colon mucosa. MI-1 could inhibit Syk in vitro, so its anti-inflammatory effects could be realized through signaling pathways which involve Syk.…”
Section: Discussionmentioning
confidence: 99%
“…7 of the 43 candidates were published relevant to IBD. Azacitidine (DNA methyltransferase inhibitor) 51 , ISOX (HDAC inhibitor) 52 , ascorbic-acid (antioxidant) 53 , cosmosiin (cytochrome P450 inhibitor) 54 , IB-MECA (adenosine receptor agonist) 55 , fostamatinib (SYK inhibitor) 56 , and iloprost (platelet aggregation inhibitor) 57 have been used as a treatment or providing protective effects for IBD.…”
Section: Resultsmentioning
confidence: 99%
“…The adenosine receptor agonist IB-MECA was shown to alleviate inflammation in DSS-induced colitis and spontaneous colitis found in IL-10-deficient mice 55 . Fostamatinib, an SYK inhibitor, reduced the inflammatory damage in the acetic acid-induced colitis 56 . Platelet aggregation inhibitor iloprost has been demonstrated to be an antioxidant and protective against colitis induced oxidative stress in experimental colitis 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Fostamatinib can selectively abrogate the BCR signaling pathway. Fostamatinib has potent anti-inflammatory effects [ 18 , 26 ]. It was first demonstrated to have activities in rheumatoid arthritis and immune thrombocytopenia [ 11 , 27 31 ].…”
Section: Syk Inhibitorsmentioning
confidence: 99%